A Wide Wavelength Range of 1 × 8 Optical Power Splitter With an Imbalance of Less Than ±1.0 dB on Silicon-on-Insulator Technology - Guofang Fan; Yuan Li; Bing Han (IEEE Photonics Journal)
A 1 × 8 optical splitter on silicon-on-insulator technology is demonstrated with less than ±1.0 dB imbalance for a wavelength range of 300 nm, in which, a multimode interference (MMI) structure is introduced into an optical power splitter. A comparison is provided for 1 × 2 MMI splitters with and without tapers, a 1 × 2 MMI splitter with tapers is designed, fabricated and measured, which show a wider wavelength range of 300 nm with a lower imbalance of less than ±0.25 dB and a propagation loss of 3 dB.